2007
DOI: 10.2118/98236-pa
|View full text |Cite
|
Sign up to set email alerts
|

Fracture-Related Diagenesis May Impact Conductivity

Abstract: Summary Rapid loss of fracture conductivity after hydraulic fracture stimulation has often been attributed to the migration of formation fines into the proppant pack or the generation of fines derived from proppant crushing. Generation of crystalline and amorphous porosity-filling minerals can occur within the proppant pack because of chemical compositional differences between the proppant and the formation, and the compaction of the proppant bed because of proppant pressure solution reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…However, this operation can only alleviate the decrease rate of the fracture conductivity. The conductivity will eventually decrease [31][32][33][34]. Previous studies suggest that the fracture conductivity decreases rapidly during the first couple of days and for the rest of the time the decline degree remains very small ( Figure 1).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, this operation can only alleviate the decrease rate of the fracture conductivity. The conductivity will eventually decrease [31][32][33][34]. Previous studies suggest that the fracture conductivity decreases rapidly during the first couple of days and for the rest of the time the decline degree remains very small ( Figure 1).…”
Section: Introductionmentioning
confidence: 82%
“…Although it is well documented that the fracture conductivity decreases rapidly at first and tends to converge asymptotically [31][32][33][34]37], previous studies always assumed that hydraulic fractures do not vary with time. Below, we analyze the difference between time-independent and time-dependent fractures.…”
Section: Effect Of Initial Fracture Conductivitymentioning
confidence: 99%
“…This product was resulted from the difference in chemical composition between the proppant and the formation, and the compaction of the proppant bed due to proppant-pressure solution reactions. Weaver et al (2007) found that this damage mechanism, proppant diagenesis, has a major impact on fracture conductivity and is more significant in high temperature and high stress wells. Akrad et al (2011) studied the effect of fracturing fluids on shale rock mechanical properties.…”
Section: Rock/fluid Interactions and Proppant Embedmentmentioning
confidence: 99%
“…Obviously, it is not possible to control the diagenesis of natural rock formations. However, it was recently found that bauxite or ceramic proppants are likewise susceptible to diagenesis (Weaver et al 2007). It is also known that water is a basic ingredient for chemical degradation; therefore, especially for deep formations (e.g., hot and high stresses), it is important that all proppants be protected by polymeric shells, such as resin coating or other hydrophobic shell.…”
Section: Diagenesismentioning
confidence: 99%